Combination pharmacotherapies for cardiac reverse remodeling in heart failure patients with reduced ejection fraction: A systematic review and network meta-analysis of randomized clinical trials. (July 2021) - Bao, Jieli; Kan, Rongsheng; Chen, Junhong; Xuan, Haochen; Wang, Chaofan; Li, Dongye; Xu, Tongda
Abstract: Pharmacotherapies, including angiotensin-converting enzyme inhibitors (ACEIs), angiotensin receptor II blockers (ARBs), β-blockers (BBs), mineralocorticoid receptor antagonists (MRAs) and angiotensin receptor blocker-neprilysin inhibitor (ARNI), have played a pivotal role in reducing in-hospital and mortality in heart failure patients with reduced ejection fraction (HFrEF). However, effects of the five drug categories used alone or in combination for cardiac reverse remodeling (CRR) in these patients have not been systematically evaluated. A Bayesian network meta-analysis was conducted based on 55 randomized controlled trials published between 1989 and 2019 involving 12, 727 patients from PubMed, EMBASE, Cochrane Library, and Clinicaltrials.gov. The study is registered with PROSPERO (CRD42020170457). Our primary outcomes were CRR indicators, including changes of left ventricular ejection fraction (LVEF), left ventricular end-diastolic volume (LVEDV) and end-systolic volume (LVESV), indexed LVEDV (LVEDVI) and LVESV (LVESVI), and left ventricular end-diastolic dimension (LVEDD) and end-systolic dimension (LVESD); Secondary outcomes were functional capacity comprising New York Heart Association (NYHA) class and 6-min walking distance (6MWD); cardiac biomarkers involving B type natriuretic peptide (BNP) and N-terminal pro–BNP (NT-proBNP). The effect sizes were presented as the mean difference with 95% credible intervals. According to the results, all dual-combination therapies except ACEI+ARB were significantly more associated with LVEF or NYHA improvement than placebo, ARB+BB and ARNI+BB were the top two effective dual-combinations in LVEF improvement (+7.59% [+4.27, +11.25] and +7.31% [+3.93, +10.97] respectively); ACEI+BB was shown to be superior to ACEI in reducing LVEDVI and LVESVI (−6.88 mL/m 2 [−13.18, −1.89] and −10.64 mL/m 2 [−18.73, −3.54] respectively); ARNI+BB showed superiority over ACEI+BB in decreasing the level of NT-proBNP (−240.11 pg/mL [−456.57, −6.73]). All tri-combinations were significantly more effective than placebo in LVEF improvement, and ARNI+BB+MRA ranked first (+21.13% [+14.34, +28.13]); ACEI+BB+MRA was significantly more associated with a decrease in LVEDD than ACEI (−6.57 mm [−13.10, −0.84]). A sensitivity analysis ignoring concomitant therapies for LVEF illustrated that all the five drug types except ARB were shown to be superior to placebo, and ARNI ranked first (+4.83% [+1.75, +7.99]). In conclusion, combination therapies exert more benefits on CRR for patients with HFrEF. Among them, ARNI+BB, ARB+BB, ARNI+BB+MRA and ARB+BB+MRA were the top two effective dual and triple combinations in LVEF improvement, respectively; The new "Golden Triangle" of ARNI+BB+MRA was shown to be superior to ACEI+BB+MRA or ARB+BB+MRA in LVEF improvement. Graphical Abstract: ga1